FGF8 isoform b expression in human prostate cancer. - Gnanapragasam, V; Robinson, M; Marsh, C; Robson, C; Hamdy, F; Leung, H (2003)
Overexpression of fibroblast growth factor 8 (FGF8) mRNA has been previously described in prostate cancer. Of its four isoforms, FGF8b is thought to be the most important in carcinogenesis. We hypothesised that immunodetection of FGF8b in archival prostate cancer specimens is of potential prognostic value. Using a selected cohort of prostate tumours from transurethral (n=30) and radical prostatectomies (n=59), an optimised protocol for FGF8b immunoreactivity was used to corroborate expression with clinical parameters. No expression was observed in benign prostates (n=10). In prostate cancer, immunoreactivity was localised to the malignant epithelium with weak signals in the adjacent stroma. Expression of FGF8b in stage T1 and T2 cancers were 40 and 67%, respectively. In contrast, FGF8b expression was present in 94% of T3 and 100% of T4 cancers. By histological grade, FGF8b was found in 41% of low-grade cancers (Gleason score 4-6), 60% of intermediate-grade cancers (Gleason score 7 and 92% of high-grade cancers (Gleason score 8-10). The intensity of expression was significantly associated with stage (P=0.0004) and grade (P<0.0001) of disease. We further hypothesised that FGF8b overexpression resulted from enhanced transcription and translation rather than from abnormalities involving the FGF8 gene locus. This was tested by means of fluorescent in situ hybridisation in 20 cancer specimens to map the FGF8 gene locus. FGF8 gene copy number in benign and malignant nuclei was found to be similar (2.33+/-0.57 and 2.0+/-0.81, respectively P=0.51). Based on these findings, we propose a multicentre study on cohorts of patients to further evaluate FGF8b as a potential prognostic marker in prostate cancer.